Association of C-reactive Protein in Preeclampsia (Medicine Today, 2024)
Introduction: Preeclampsia is a multisystemic disorder that complicate about 7-10 percent of human pregnancies.Worldwide this syndrome contributes high maternal and perinatal mortality and morbidity. C-reactive protein, a marker of tissue damage and inflammation, is elevated in seurm in overt preeclampsia. It is used as an objective and sensitive index of overall inflammatory activities in the body. Aims and Objectives: To explore the association of C-reactive protein level with the preeclampsia patients. Materials and Methods: The present study was a Case–Control study, conducted in the Department of Obstetrics and Gynaecology in collaboration with the Department of clinical pathology of Sir Salimullah Medical College Hospital, Mitford, Dhaka during the period of January 2013 to December 2013.The study population was pregnant women with preeclampsia and normal term pregnant patients admitted during study period. A total of 66 patients were included in the study. Among them 33 were clinically diagnosed preeclampsia women grouped as Cases and another 33 were age, parity and BMI matched term pregnant women as Controls. Eastmation of serum C-reactive protein was done by Nyco Card Reader-II method (Appendix-11). Statisticians analysis was perform by using SPSS. Results: C-reactive protein concentration (mg/L) was found significantly higher (p